Opioid use disorder in chronic non-cancer pain in Germany: a cross sectional study. Issue 4 (3rd April 2019) - Just, Johannes Maximilian; Schwerbrock, Fabian; Bleckwenn, Markus; Schnakenberg, Rieke; Weckbecker, Klaus
Abstract : Objectives: The DSM-5 diagnosis 'opioid use disorder' (OUD) was established to better describe and detect significant impairment or distress related to opioid use. There is no data on rates of OUD in chronic non-cancer pain (CNCP) in European countries. Therefore, our objective was to screen patients in specialised pain centres for signs of OUD. Design: Cross-sectional questionnaire study. Setting: Four outpatient pain clinics in the area of Bonn, Germany. Participants: n=204 patients participated in the study (response rate: 87.9%). All adult patients with opioid pain therapy >6 months for CNCP were included. Excluded were patients with malignant disease, patients who could not collect their prescription themselves due to age or multimorbidity and patients on opioid-maintenance therapy. Primary and secondary outcome measure: Primary outcome measure was the proportion of patients with mild to severe OUD. Results: One-fourth (26.5%) of participants were diagnosed with OUD. Moderate to severe disorder was found in 9.3. Young age was the only connected risk factor (OR 0.96 [95% CI 0.94 to 0.99], p: 0.003). Conclusions: OUD is a relevant diagnosis in patients on long-term opioid therapy for CNCP in the Bonn area. Careful follow-up by the attending physicians is advisable, especially in patients with moderate or severe disorder.